Relationship Between Integrated Marketing Capability on Sales and Brand Performance: Moderation Roles of IMC Performance (Malaysian Management Journal, 2016)
Due to in the fierce competition in the fast moving consumers good (FMCG) industry and lack of growing demand in recent years in this industry, firms are now looking for more efficient and effective ways of creating value for their brands. In this regard, integrated marketing communication (IMC) is a newly introduced concept which has not been thoroughly investigated in the FMCG market of Iran. Therefore, the aims of this study are twofold, first, is to empirically examine the influence of IMC capability of the organization on the brand and sales performance. Second, is the investigation of the moderation role of the IMC performance which is not covered in the literature. The detergent industry was investigated by choosing one of the biggest detergent players in Iran, and the sample of brand, advertising and marketing managers, and experts were considered for distribution of the questionnaire. The results support the effect of IMC capability on sales and brand performance. Moreover, the analysis showed support for moderation role of IMC performance. Managerial implications are discussed at the last section of this research.